Entrepreneurship Development Strategy Based on Local Awareness in Making Community Welfare (A Study in Disperindagkop Central Aceh) - Lukmannul Haqim; Ika Hartika (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
Abundant natural resources are not a guarantee for the welfare of the people in a country. Another most important aspect in achieving prosperity is the strength of its human resources. Entrepreneurship as a solution in improving the standard of human life needs to be considered as an alternative. One of the roles of government in forming an entrepreneurial society has been carried out by Disperindagkop. Coffee is one of the commodities in Central Aceh. By creating more value from coffee, it is hoped that the people of Central Aceh will be able to increase their income. In making decisions requires a variety of considerations and careful design. ANP is a qualitative method for a decision-making process with a general framework without making assumptions about the independence of elements at a higher level than those at lower levels and about the independence of elements at a level. By using ANP, we know in detail which things are the most priority or important of problems, strategies and solutions, because sometimes there are a lot of policies or policy making, there are many limitations related to resources, so we need to know and understand which ones should be the first key / main problem or main strategy. After testing with ANP, it is found that the most priority aspect in determining the entrepreneurship development strategy is based on local wisdom is the entrepreneur / community, followed by Disperindag and the last one is academics. Creating individuals who have an entrepreneurship spirit is not an easy job. It takes a variety of education and training related to entrepreneurs and has become part of the government's responsibility for the welfare of its people, and one way is to educate people to become strong entrepreneurs.